O różnych aspektach staropolskiej biesiady w świetle relacji literackich - Wichowa, Maria (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2002)
This study contains some comments on the Old Polish Convival gathering in the light of litetary relations. The author pionted a few aspects o f the concept “ convival gathering” , which used to function in the age o f Renaissance and Baroque. Than she carried out the analysis o f Anonim Protestant’s work titled Biesiada o dobrym gospodarzu, setting it in the wide literary and cultural background. She proved that the poet created plebeian inapproval satire, that he was not the uncritical admirer of life in “ the pecelul and jouful county". He also had the tendency to hyperbolize phenomena pictures from the social life. However, everything that was the subject of criticism for the 16th century critics, in the plebeian and epistolary literature o f 17th and 18th century was seen and was presented as the social norm.